THE IMPACT OF BANK-SPECIFIC FACTORS ON NON-PERFORMING LOAN IN INDONESIA: EVIDENCE FROM ARDL MODEL APPROACH - Sinay, Lexy Janzen; Latupeirissa, Sanlly J; Pelu, Shelma M; Tilukay, Meilin I (PATTIMURA UNIVERSITY, 2022)
Non-performing Loan (NPL) is an indicator that is generally used to determine the ability of bank management to manage non-performing loans. This study aims to analyze the impact of bank-specific factors on NPL. The bank-specific factors are Capital Adequacy Ratio (CAR), Return on Assets (ROA), Operating Expenses on Operating Income (BOPO), and Loan to Deposit Ratio (LDR). The data used is monthly time series data, a case study on Commercial Banks in Indonesia from January 2015 to August 2020. The model used to analyze these problems is Autoregressive Distributed Lag (ARDL). The results obtained are ARDL(1,6,0,1,1) model is the best model. The model shows that bank-specific factors have a direct impact on NPL. Specifically, the ARDL bounds test offers the analysis results, which show that the ability of bank-specific factors to explain the NPL of commercial banks in Indonesia is 84%. At the same time, 16% are other factors outside the model. The analysis results show a long-run cointegration relationship between NPL and specific characteristics, CAR, ROA, and BOPO. Then, only CAR, BOPO, and LDR impact NPL in the short-run relationship. The equilibrium correction obtained is significant and confirms a long-run relationship. The equilibrium correction indicates a high velocity towards stability after a shock. It means that the performance of Commercial Banks in Indonesia is outstanding during the COVID-19 Pandemic because the ability to recover from shock is relatively faster